ECONOMIC AND ENERGY EFFICIENCY OF THE USE OF BIOLOGIZED AGROTECHNOLOGIES FOR CORN CULTIVATION - Yaroslav HADZALO; Yaroslav LIKAR; Raisa VOZHEHOVA; Tetіana MARCHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was conducted in 2017–2019 at the experimental field of the Institute of Irrigated Agriculture of NAAS (now the Institute of Climate-Smart Agriculture of the National Academy of Agrarian Sciences of Ukraine). Factor A studied different maturity groups of corn hybrids selected by the Institute of Irrigated Agriculture of the NAAS:Stepovyi, Skadovs'kyi, Inhul's'kyi, Chonhar, Arabat. Factor B – protection system: control, water treatment; biological; chemical; integrated. The highest conditionally net profit and profitability of hybrids of all FAO groups was observed under the integrated method of plant protection. The maximum value of conditional net profit is 2.26 and 3.26 thousand euro ha-1 was observed in mid-late hybrids Chonhar (FAO 420) and Arabat (FAO 430) under integrated plant protection systems. The mid-late Arabat hybrid (FAO 430) showed the maximum level of profitability of 117–141%. It is most economically profitable to grow mid-late hybrids Chonhar (FAO 420) and Arabat (FAO 430) under systems of integrated plant protection.